Manajemen Pelayanan Kefarmasian terhadap Pengaruh Penggunaan Antibiotik RSUD Haji Padjonga Daeng Ngalle - Gemy Nastity Handayany; Nurhamida Nurhamida (Lembaga Pengembangan Kinerja Dosen, 2026)
Pharmaceutical services are seen as a form of professional service carried out directly by pharmacists with full responsibility to patients and improving the quality of life of patients. The problem of irrational use of antibiotics remains a serious issue both at the national and global levels, because it can cause resistance, therapeutic failure, and increase the burden on public health. The study aims to analyze the relationship between pharmaceutical service management and the level of rationality of antibiotic use at Takalar District Hospital. The research method used is a mixed method, which combines qualitative and quantitative techniques to obtain a more comprehensive picture. The research instruments include structured questionnaires and short interviews as a complement to deepen the data. The sampling technique was carried out using a purposive sampling method, so that 99 respondents were obtained who were inpatients using antibiotics who met the predetermined inclusion criteria. The variables used were Reliability (X1), Perception (X2), Assurance (X3), Tangible (X4) and Rationality of Antibiotic Drugs (Y1) with data analysis using SmartPLS 4.0. The results show that Reliability is a highly influential factor in the rationality of antibiotic use, with a path coefficient of 0.352. While Perception is not significant, with a path coefficient of -0.000. The Assurance variable has a path coefficient of 0.158, followed by the Tangible variable with a path coefficient of 0.112. In conclusion, Reliability, Assurance, and Tangible significantly influence the rationality of antibiotic use at Takalar District Hospital.